2018
DOI: 10.1097/brs.0000000000002531
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Kyphoplasty

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…PVP research nowadays focuses mostly on comparing the effects and consequences of unilateral versus bilateral penetration. Yilmaz [ 5 ] found that there was no significant difference between pain alleviation and vertebral height improvement between unilateral and bilateral puncture. However, unilateral puncture takes much less time, has less bone cement injection, and takes longer to puncture.…”
Section: Introductionmentioning
confidence: 99%
“…PVP research nowadays focuses mostly on comparing the effects and consequences of unilateral versus bilateral penetration. Yilmaz [ 5 ] found that there was no significant difference between pain alleviation and vertebral height improvement between unilateral and bilateral puncture. However, unilateral puncture takes much less time, has less bone cement injection, and takes longer to puncture.…”
Section: Introductionmentioning
confidence: 99%
“…Complications of PKP surgery primarily included bone cement leakage, puncture damage to surrounding structures (facet joints, spinal cord, and blood vessels), and pulmonary embolism. 23 The rate of bone cement leakage was not significantly different in the two groups. This supported the fact that the rate of bone cement leakage is not associated with the puncture approach of PKP.…”
mentioning
confidence: 78%
“…PKP injects bone cement into the injured vertebrae through a working channel, effectively restoring vertebral height in a short period time, relieving symptoms such as low back pain, greatly shortening the patients' bed rest and reducing the occurrence of long-term bed rest complications like deep vein thrombosis, hypostatic pneumonia, decubitus and disuse muscular atrophy[8, 21,22]. PKP works through the pedicle, and most studies have shown that the unilateral approach has similar e cacy compared to the bilateral approach, but the former in quicker, less invasive, less expensive and has a lower risk of cement leakage and displacement [23,24]. In this study, a unilateral approach via the pedicle was adopted.…”
Section: Discussionmentioning
confidence: 99%